ESTIMATION OF S-WAVE VELOCITY STRUCTURES IN YOGYAKARTA BASIN, INDONESIA - Tun Naing; Subagyo Pramumijoyo; Hiroshi Kawase (Geological Engineering Department Universitas Gadjah Mada, 2015)
For the theoretical simulation or prediction of strong ground motion, it is prime importance to get information of underground structures, especially for sedimentary layers overlying on bedrock, like in Yogyakarta Basin. The Standard Penetration Test, Spectral Analysis of Surface Wave (SASW) and other geotechnical properties are used to estimate S–wave velocity structures in this basin. SPT tests were conducted at nine sites and SASW measurements were performed at seventeen sites. As a result, the S-wave velocity structures of top 30 m depth had been evaluated in each site. The average shear wave velocity v30 s had been successful estimated and the sites are classified into three types; soft soil, medium dense soil and hard soil. All sites where SPT performed are on soft soil according to their v30 s . However, according to v30 s from SASW measurements, 10 sites are located on medium dense soils type, 5 sites on dense soils and 2 sites on soft soils. The acceptable equivalent S-wave velocitystructure is observed by comparing the results from SASW and geotechnical approach in Imogiri, Bambang Lipuro, Pundong (Watu, Pranti) and Pandak (Wijirejo) areas. Keywords: Ground motion, underground structure, sedimentary layer, SPT, SASW, Pundong